Educational Platforms and Tools and Their Application Teaching in The Virtual Classroom - Gallegos Valdés, Claudia María
New technologies including overhead projectors, interactive whiteboards, computers and wireless internet have opened up the classroom to the outside world. The teaching-learning process has to adapt to changing learning contexts. Technology provides a learner independent in language learning. Thus, technology enables the learner’s efforts easier and faster. At present, there are several online services and some of them are free. It is possible that many more services will be available in future. The purpose of this study is to show what students learn during the course called ‘‘Management Of Virtual Environments For Teaching And Learning Of Foreign Languages’’. This Specialization Course consisted to know and learn the use of different virtual platforms, tools and websites, that can be use in a virtual environment. This was divided in three modules: 1) Online English Language Teaching, 2) Educational Applications for Learning a Foreign Language, 3) The Design of Didactic Materials for Virtual Environments. Students were capable to create didactic materials by making use of infographics, video editing, podcast, interactive image and others; and show the potential of technologies for teaching a second language. The report will include description of some of the tools used such as Canva, Padlet, Nearpod, Kahoot, Flippity, Flipgrid, Powtoon, Liveworksheets and Edpuzzle and also some educational platforms such as Moodle, Classroom, Google Site, and Edmodo. Keywords: Language Learning ; Educational Tools ; Education Technology.